(untitled) (Південний архів (історичні науки), 2024)
The purpose of the study is to analyse the impact of the mass resistance of the peasantry during the years of continuous collectivisation and the Holodomor of 1932–1933 on the transformation of the Marxist-Stalinist (Bolshevik) project of communist assault and the essence of the communist project itself. Although in Soviet literature, the Soviet-communist system was called socialism, in Stalin’s time, it was about building communism. Research methods: multifactorial analysis of the factors (ideological, political, socio-economic, moral and psychological) that influenced the policy of the Stalinist leadership and the resistance of the peasantry to Stalinism in 1929–1933. The multifactorial analysis has become the key to understanding the impact of the consequences of the compromise between the government and the peasantry on the nature of Ukraine’s further development in the Soviet era. The results of the study prove that the consequences of the mass resistance of the peasantry had a significant impact on Stalin’s project of communist assault. The Ukrainian peasantry, deprived of leaders, weapons and political leadership, fought desperately for themselves, their children and their descendants against the ruthless repressive machine of Soviet totalitarianism. The peasantry fought for many years, used active and passive forms, fought hard and suffered millions of losses. Formally, Stalin’s collectivisation was defeated, and the peasantry was clamped in the grip of the administrative command system, subdued by the Holodomor of 1932–1933 and the poverty of real socialism. Nevertheless, the peasants managed to defend the right of personal ownership of their homesteads and defended the agricultural collective farm as a lesser evil in comparison to the communes, whose domination the Bolsheviks sought to impose on the peasants. At the same time, in cities, workers won the right to choose their place of work. Conclusions: It is emphasised that these islands of “non-communism” led to the preservation, albeit in hybrid forms, of private property, the market and commodity-money relations. Private property and the market allowed the communist-Soviet regime to survive for another 60 years. Still, it was they who eventually sent the Soviet regime and real socialism to the dustbin of history.